2019
DOI: 10.3389/fphys.2019.00086
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein Is Elevated Only in High Creatine Kinase Responders to Muscle Damaging Exercise

Abstract: The purpose of this study was to investigate if exertional rhabdomyolysis induced by an acute bout of plyometric exercise in untrained individuals was associated with histological characteristics of skeletal muscle, creatine kinase (CK) polymorphism or secondary damage. Twenty-six healthy male untrained individuals completed a bout of plyometric exercise (10 sets of 10 maximal squat jumps, with each standardized to achieve at least 95% of individual maximal jump height). Blood samples were taken, and perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 44 publications
2
25
1
Order By: Relevance
“…Among them is the fact that plasma interleukin-6 (IL-6) was not measured, as this represents a reliable biochemical parameter for assessing inflammation induced by exercise and EIMD [76]. Moreover, C-reactive protein is an acute phase protein produced by the liver in response to IL-6 increases during systemic inflammation and is dependent on several factors such as individual response [77]. Along these lines, it has been demonstrated that CHO intake influences IL-6 but not C-reactive protein following a 32 km mountain trail race [66] and, therefore, it might have been interesting to measure these parameters.…”
Section: Limitations Strengths and Future Linesmentioning
confidence: 99%
“…Among them is the fact that plasma interleukin-6 (IL-6) was not measured, as this represents a reliable biochemical parameter for assessing inflammation induced by exercise and EIMD [76]. Moreover, C-reactive protein is an acute phase protein produced by the liver in response to IL-6 increases during systemic inflammation and is dependent on several factors such as individual response [77]. Along these lines, it has been demonstrated that CHO intake influences IL-6 but not C-reactive protein following a 32 km mountain trail race [66] and, therefore, it might have been interesting to measure these parameters.…”
Section: Limitations Strengths and Future Linesmentioning
confidence: 99%
“…One study by Isaacs et al describes that only "high responders", those whose creatine kinase (CK)increased above 1000 U/L after muscle damaging exercise, had a corresponding increase in Mb. It was also noted that only "high responders" also increased C-reactive protein (CRP) [31]. However, those that were "low responders" did not have a corresponding increase in CK or CRP suggesting that changes in Mb, CK, and CRP have a non-linear relationship.…”
Section: Effects Of Pea Supplementationmentioning
confidence: 99%
“…Three differential proteins in the SAMS group had been reported to be associated with muscle damage since day 3. For example, i) the fibrinogen gamma chain (FIBG) increased ≥10-fold after impact trauma in the muscle tissue of male Wistar rats [32]; ii) osteopontin (OSTP) was reported to be increased in patients with idiopathic inflammatory myopathies, both in muscle and in serum [34]; and iii) C-reactive protein (CRP) was reported to be elevated only in humans with high CK levels when undergoing muscle-damaging exercise [37]. In addition, five differential proteins were associated with the mechanism of SAMS.…”
Section: Discussionmentioning
confidence: 99%